Pengaruh Persepsi Harga, Kualitas Pelayanan Dan Lokasi Terhadap Keputusan Pembelian (Studi Pada Konsumen UD Setia Makmur Malang) - Listi, Ike Ratna; Khalikussabir, Khalikussabir; Wahyuningtyas, Nanik (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to test and determine the influence of price perceptions, service quality and location on purchasing decisions (Study on consumers of UD Setia Makmur Malang). This research is a type of quantitative research. The sampling technique used the formula from Lemeshow with the calculation results of 96 samples. The data used in this research is primary data by distributing questionnaires to visitors to the UD Setia Makmur Malang shop. To solve the problems in this research using SPSS assistance with instrument tests, namely validity and reliability tests, normality tests, analysis of classical assumption tests, namely multicollinearity tests and heteroscedasticity tests, multiple linear regression analysis, hypothesis tests, namely F tests, t tests and coefficient tests. determination. The results of this research state that price perception has a significant positive effect on purchasing decisions, service quality has a significant positive effect on purchasing decisions and location has a significant positive effect on purchasing decisions. Keywords: Price Perception, Service Quality, Location, Purchase Decision.